The Relationship of Economic Growth And Terrorism with the Human Development Index: A Causality Analysis on MENA Countries - Özcan, Günay; Karter, Cigdem (Technium Social Sciences Journal, 2020)
Examining the human development of societies is one of the important economic policy practices of recent times. Therefore, economies steer the sub-components of human development and their policies implemented by researching the factors that affect such sub-components. In this context, the aim of this study is to examine the relationship between economic growth and terrorism with human development in 12 selected MENA countries in the period of 2002-2017 by the panel causality method. The findings obtained as a result of the panel causality analysis show that both terrorism and economic growth have bidirectional causality with the human development index throughout the panel. A causality relationship has also been found in many countries on a country basis